Structure and distribution of fish assemblages at Burdwood Bank, the first Sub-Antarctic Marine Protected Area “Namuncurá” in Argentina (Southwestern Atlantic Ocean) - Delpiani, Sergio Matias; Bruno, Daniel Osvaldo; Vazquez, Diego Martin; Llompart, Facundo Manuel; Delpiani, Gabriela Elina; Fernández, Damián Andrés; Rosso, Juan Jose; Mabragaña, Ezequiel; Díaz de Astarloa, Juan Martín (Polar Biology)
The first non-coastal Sub-Antarctic Marine Protected Area (Namuncurá) in Argentina was created in 2013, at Burdwood Bank (MPAN-BB), an undersea plateau located about 200 km south from Malvinas/Falkland Islands, SW Atlantic Ocean. The main contribution of this work was to explore fish species composition and the structure of fish assemblages in three different zones of the MPAN-BB with different conservation strategies and different surrounding areas. Twenty-two fishing trawls were performed using a demersal bottom trawl pilot net at depths between 71 and 608 m. A total of 667 fish belonging to 30 species were collected in the surveyed area. The richest family in terms of species number was Nototheniidae (seven species), followed by Macrouridae, Myxinidae and Zoarcidae (four species each), then Moridae and Arhynchobatidae (three species each), and finally Muraenolepididae and Psychrolutidae (two species each). The remaining families were represented by a single species. Three significantly different fish assemblages were detected. These distinct assemblages were largely circumscribed at the plateau, the shelf-break slope, and the area west of the BB. The results showed that fish diversity in the MPAN-BB is relatively high constituting ~ 10% of the fish composition reported for the Atlantic sector of the Magellanic Province. The present data suggest that fishes are an important component of the benthic community planned to be protected by the implementation of the MPAN-BB. These findings have important implications for habitat preservation and threatened species conservation. Fil: Delpiani, Sergio Matias. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Bruno, Daniel Osvaldo. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, ...